Promoting the Principles of Ecological Ethics, Ecosociology, and Ecomusicology through the Practice of Planting Songs in the Rote Society - Pattinaja, Maryon Daniamaputra; Messakh, Merling Tonia Litron Litos Conthes; Alexander, Ferdinant; Ufi, Delsylia T.; Kwon, Kwang-Eun (Resital: Jurnal Seni Pertunjukan, 2024)
This study seeks to analyze the planting songs of the Rote society through the lenses of ecological ethics, ecosociology, and ecomusicology. The research method is qualitative ethnography, utilizing semiotic and thematic data analysis tools. From an ecological ethics perspective, the planting song is viewed as a profound expression of reverence for nature as the source of life. Maintaining ecological balance through sustainable agricultural practices reflects reverence and serves as a medium for the spiritual connection among humans, nature, and the divine.  From an ecosociological standpoint, planting songs function as a medium for social communication, encapsulating values of empathy, responsibility, and the ethos of collectivism and solidarity among farmers, widows, and orphans – social groups lacking a stable income and facing economic vulnerability. Planting songs exemplify a significant aspect of ecomusicology, functioning as a means of communication between humans and nature that encapsulates life experiences, collective cultural memory, and impressions of the natural world. A comprehensive grasp of the interplay between culture, environment, and ethical conduct underpins the sustainability of communal existence in the Rote society.